Effects of the Covid-19 Pandemic on Primary Education System of Lahore, Pakistan - Laila Shahzad, Sadia Yousaf, Nimra Riaz, Muhammad Umar Hayyat, Gulzareen Ghafoor, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The pandemic of Covid-19 impeded all socio-economical, pedagogic, and recreational activities. Pakistan is facing an intensified educational crisis due to previous educational differences, so the era of the pandemic has shown difficulties in the educational framework. Aim: Awareness among parents and students to combat challenges of pandemic. Method: The current study is based on random quantitatively study which gathered data from 300 respondents assembled from different areas of Lahore, Pakistan from June 2020 to July 2021. The responses were collected from students, teachers, and parents that how homeschooling compromises student’s physical, psychological, and emotional health. Results: About 76% of the students favoured traditional classes over online classes whereas only 20% of the students found the online session interactive. In the other section, only 15.33% of the teachers were satisfied by the online results and they complained about the poor performance and interaction with the students. Overall, 81.67% parents agreed that there is a decline in the physical activity of their children. The results of this study suggested that social distancing and the emerging challenges associated with Covid- 19 have entirely changed the education system that has caused number of problems for children, parents, and teachers in Pakistan. Practical implication: This study highlights pros and cons of online study; such studies give students and teachers a way to prepare for future challenges. Conclusion: Considering all outcomes of study, it is highlighted that policy-level interventions were needed, along with well-designed interactive courses. Hence, integrated approaches based on the mental as well as physical capabilities of the students must be executed, and e-tools must also be practiced in traditional classes to fill the gap of homeschooling. Keywords: Covid-19, Homeschooling, Friendly Tool, Psychological Pressures, Policy-level Intervention